2020
DOI: 10.1002/adfm.202008351
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Driven WSe2/Bi2O2Se Van der Waals Heterostructure Photodetectors with High Light On/Off Ratio and Fast Response

Abstract: Benefiting from the superior electron mobility and good air‐stability, the emerging layered bismuth oxyselenide (Bi2O2Se) nanosheet has received considerable attention with the promising prospects for electronics and optoelectronics applications. However, the high charge carrier concentration and bolometric effect of Bi2O2Se give rise to the high dark current and relatively slow photoresponse, which severely impede further improvement of the performance of Bi2O2Se based photodetectors. Here, a WSe2/Bi2O2Se Van… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
126
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(150 citation statements)
references
References 63 publications
(117 reference statements)
3
126
1
Order By: Relevance
“…The extracted power-dependent photocurrent (I ph ) is plotted in Fig. 4g and fitted with formula [51]:…”
Section: Articles Science China Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracted power-dependent photocurrent (I ph ) is plotted in Fig. 4g and fitted with formula [51]:…”
Section: Articles Science China Materialsmentioning
confidence: 99%
“…And the trapping sites may come from the impurities at the interface between BTS flakes and substrate, or the charge impurity states inside the transported flakes [46,52]. What is more, we calculated the responsivity (R) of the BTS photodetector according to the formula [51]: R = I ph /PS, where S is the effective channel area estimated to be 44 μm 2 as shown in Fig. S3.…”
Section: Articles Science China Materialsmentioning
confidence: 99%
“…[15] WSe 2 /Bi 2 Te 3 heterostructure has capability to get the R of 27 mA W −1 at 1550 nm wavelength as reported by H. Liu et al [16] P. Luo et al demonstrated the vdWs heterostructure comprising from WSe 2 /Bi 2 O 2 Se. They observed that fabricated device has detection ability in NIR regime up to 2000 nm but suffers from low detectivity (D*) and R. [17] Recently, PdSe 2 /WS 2 vdWs heterostructure demonstrated by J. C. Ho group exhibits broadband photoresponse from visible (532 nm) to NIR spectrum (1550 nm) but has low R, that is, 3.19 and 0.019 mA W −1 at visible (635 nm) and NIR (1550 nm) spectrum, respectively. [18] Interlayer coupling has a significant influence on the electronic/ optic performance of vdWs heterojunction devices, and strong interlayer coupling in 2D vdWs heterojunction is always desirable for efficient charge transfer and high-speed response.…”
Section: Introductionmentioning
confidence: 99%
“…While conventional heterojunction photodetectors show great advantages, they have difficulty covering a broad spectrum in terms of spectral response due to bandgap limitations [139][140][141][142]. Huang et al developed a PtTe 2 /graphene heterostructured photodetector (Figure 9d) [102].…”
Section: D Materials Heterostructurementioning
confidence: 99%